Islamisasi Ilmu Pengetahuan dan Pengilmuan Islam - Sumiran, Sumiran; Prasetyo, Dony Agus; Zarkasyi, Muhammad Badruddin; Setyawati, Hidayati Rina (Lembaga Yasin AlSys, 2026)
The discourse on the Islamization of knowledge has emerged as a response to the dominance of modern science shaped by Western secularism and a predominantly materialistic outlook that separates the spiritual dimension from the structure of knowledge, even though the golden age of Islamic civilization in the 7th–14th centuries demonstrated an integrative model linking revelation, reason, and the advancement of knowledge. This article aims to examine the concept of the Islamization of knowledge as an effort to integrate Islamic values into modern science by explaining its historical background, formulating the main objectives of Islamization, and outlining the methodological characteristics and differences in approach among its principal proponents. The study is based on a critical analysis of the ideas of thinkers such as Muhammad Iqbal, Syed Hossein Nasr, Syed Muhammad Naquib al-Attas, and Ismail Raji al-Faruqi as reflected in their works and related literature. The findings show that the main objectives of the Islamization of knowledge are to protect Muslims from misleading forms of knowledge, to restore the dimension of tauhid and the metaphysical within the structure of knowledge, and to build an integral synthesis between revelation, reason, and intuition. Conceptually, the process of Islamization is explained through dewesternization (the removal of secular elements), the reconstruction of disciplines on the basis of the Islamic worldview, integratisation (the integration of revelation and reason), and objectification so that knowledge functions as a mercy for all humankind. Differences in approach are evident in al-Attas’s emphasis on the transformation of the subject through adab, whereas al-Faruqi stresses the reconstruction of the object of knowledge through the systematic integration of modern disciplines with the Islamic intellectual heritage. This study concludes that the Islamization of knowledge is necessary for building an integral Islamic civilization grounded in tauhid and capable of responding to the challenges of modernity without losing its religious essence, while also offering a normative and methodological framework for the development of knowledge that is both integral and humanistic.